EFEKTIVITAS SKILL ANALISIS DAN PENGETAHUAN AWAL TERHADAP KEMAMPUAN PENULISAN ARGUMENTATIF SISWA: Nabila Alya Rahmah*, Pipit Novita - NABILA ALYA RAHMAH; Novita, Pipit (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
This research aims to investigate the effect of analytical and prior knowledge towards student’s argumentative writing ability at Grade XI Senior High School. The method used in this study was quantitative research method with pre-experimental design by using pre-test, treatment and post-test as the instruments of collecting the data. The research was conducted at Daaruttaqwa Islamic Boarding School Cibinong. The sample technique used only one class of XI Grade. And the data was analysed statistically by using paired sample t-test. The study revealed a significant increase in students' pre-test and post-test scores, with a mean increase of 6.0333. The eta squared statistics indicated a large effect size. The paired sample ttable showed a significant difference, rejecting the hypothesis (Ho) and accepting (Ha). The alternative hypothesis (Ha) was approved, indicating that students' analytical and prior knowledge affects their argumentative writing abilities.